Front Cover: Translating Immunopeptidomics to Immunotherapy‐Decision‐Making for Patient and Personalized Target Selection. Issue 12 (27th June 2018) - Fritsche, Jens; Rakitsch, Barbara; Hoffgaard, Franziska; Römer, Michael; Schuster, Heiko; Kowalewski, Daniel J.; Priemer, Martin; Stos‐Zweifel, Vlatka; Hörzer, Helen; Satelli, Arun; Sonntag, Annika; Goldfinger, Valentina; et al.
Abstract : DOI:10.1002/pmic.201700284 Translation from immunopeptidomics to HLA peptide target to TCR lead to cancer immunotherapy. Cancer antigen Ag007‐01 (blue) bound to HLA‐A*02:01 (red) recognized by ACTengine™ IMA201 T‐cell receptor (green) is currently investigated in ACT trial NCT03247309. Ag007‐01 is detected on squamous NSCLC by LC‐MS/MS shown as heatmap (m/z vs retention time). This is reported in article number1700284 by Fritsche et al. TCR homology model (Modeller, UCSF) and peptide‐MHC crystal structure rendered with Chimera (UCSF) by Mathias Ferber.